Implementation of SDGs in Gunung Muda Village: Challenges and Achievement Strategies - Zakiyah, Ummi; Hidayat, Wahyu; Oktaviani, Lisa; Harvina, Fadilla (Journal Public Policy, 2024)
Sustainable development is an integrated effort to build an economy, society, environment, and governance that impact the present and future. SDGs, or Sustainable Development Goals, are a set of 17 goals established by the United Nations (UN) to achieve sustainable development by 2030. The objective of this research is to understand the implementation of the SDGs in Gunung Muda village, Belinyu district. The research employs qualitative methods with data collection techniques through interviews and focus group discussions. The implementation of sustainable development or village SDGs has been underway since 2021. From the beginning of SDGs implementation in 2021 to 2023, numerous issues still hinder achieving a good SDGs Village score, such as constraints related to budget sources, human resources, managerial resources, and infrastructure. However, Gunung Muda village has successfully implemented the SDGs in the indicator of good health and well-being through stunting prevention activities and community empowerment programs. Aspects of planning, policy-making, budgeting, and leadership support the strengthening of village government capacity in carrying out the SDGs in Gunung Muda village. The efforts and commitment of Gunung Muda village in involving the community, formulating inclusive policies, and allocating resources wisely are key factors in achieving sustainable development goals at the local level. With a deep understanding of the challenges faced, Gunung Muda village can continue to improve strategies and programs to better achieve the village SDGs targets in the future.